Artificial Intelligence Adoption and Career Reconfiguration of Office Workers: The Mediating Role of Training and Organizational Support - Dony Ari Nugroho (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The development of artificial intelligence (AI) is fundamentally reshaping workforce structures, particularly for office workers whose task profiles are highly exposed to automation-driven transformation. As organizations integrate AI into operational systems, employees increasingly face shifts in task composition, skill requirements, and long-term career trajectories. Objective: This study aims to explore the impact of AI on career shifts within the office sector. Methods: By adopting a quantitative research method through surveys and secondary data analysis, this study examines how office workers respond to changes caused by the adoption of AI in their work environments. Results: The findings indicate that AI adoption significantly reshaped task profiles for 73% of respondents, particularly affecting routine data processing, administrative tasks, and scheduling activities. Multiple regression results show that skills training is the strongest predictor of career adaptation (beta = 0.412, p = 0.002), followed by organizational support (beta= 0.389, p = 0.005), openness to technology (beta= 0.367, p = 0.003), and readiness to change (beta = 0.298, p = 0.011). Together, these variables explain 61% of the variance in adaptive outcomes (R² = 0.61). Mediation analysis further confirms that training and organizational support significantly mediate the relationship between AI adoption and career shifts. Conclusion: AI's career impact is organizationally mediated rather than technologically predetermined. The study introduces career reconfiguration as a framework explaining intra-role task transformation, extending existing career mobility and job transition theories while highlighting the importance of institutional support for workforce adaptation in AI-integrated workplaces.